The Effect Of Recruitment, Placement, And Compensation Of Outsourcing Employees Performance In The Ministry Of Manpower Republic Of Indonesia - Sri Rahayu (Jurnal Ketenagakerjaan, 2017)
The purpose of this study was to determine the influential recruitment procedures, placement, and compensation for the performance of outsourced employees, especially against a cleaning service employee at the Ministry of Manpower. The survey used in this study using multiple correlationanalysis with a total sample of 48 randomly selected employees. The results of this study indicate that the performance of outsourced parts cleaning service employees positively influenced by the recruitment, placement and compensation. Based on these findings it can be concluded that any changes or variations that occur in the performance of outsourced employees will be affected by the recruitment, placement, and compensation. Therefore, the performance of outsourced employees in the recruitment, placement, and compensation should be included in the strategic plan of the development of human resources.